Implementasi Media Pembelajaran Virtual Berbasis Geogebra dalam Mengajarkan Unsur-unsur Lingkaran Di SMAN 3 Takalar - Amrin, Irfan Pratama; Nasrullah; Alimuddin, Fauziyyah (CV. Insight Publisher, 2025)
This study aims to develop and evaluate the effectiveness of a GeoGebra-based virtual learning medium in improving students' conceptual understanding of the elements of a circle, including radius, diameter, arc, sector, and segment, as well as their ability to calculate area and circumference. Using a Classroom Action Research design, this study was conducted through structured learning stages consisting of Identifying, Observing, and Concluding. Students were actively engaged in exploration, visual construction, and reflection through the use of GeoGebra integrated into digital worksheets (LKPD). Data were collected through observation and student questionnaires and analyzed using qualitative thematic analysis. The findings indicate that the use of GeoGebra significantly enhances student engagement and understanding of abstract mathematical concepts by enabling direct interaction and visualization. Most students demonstrated improved abilities in defining and representing the elements of a circle, as well as calculating area and circumference independently. Moreover, the integration of reflective activities strengthened conceptual understanding and promoted student-centered learning. Although implementation was deemed effective, this study also identified several challenges such as students' initial unfamiliarity with the GeoGebra interface and technical limitations related to internet access and digital devices. These results suggest that GeoGebra is a powerful constructivist tool in mathematics education, provided it is supported by clear instructional guidance and adequate technological infrastructure. This research contributes to addressing the gap in the application of GeoGebra in circle geometry instruction at the secondary education level, particularly in promoting exploratory and reflective learning through digital worksheets.